Corrosion Structural metals and alloys (2019-2020) - Iannuzzi, Mariano; Lachowicz, Marzena Malgorzata; Kolisnychenko, Stanislav (Trans Tech Publications Ltd, 2021)
This issue from the topic series "Corrosion" contains articles published by Trans Tech Publications in the 2019 - 2020 years. The volume presents readers with a wide range of scientific research results and engineering solutions in studying corrosion properties and corrosion behaviour of structural metals and alloys. This collection will be useful and interesting to a broad audience of researchers and engineers from various modern manufacturing areas. Corrosion, Pitting, Rust, Intergranular Corrosion, Crevice Corrosion, High-Temperature Corrosion, Corrosion Resistance, Electrochemical Behaviour, Corrosive Environment, Heat Treatment, Embrittlement, Potentiodynamic Polarization, Stress Corrosion Cracking, Mechanical Properties, Steel, Alloy, Corrosion Rate, Electrochemical Corrosion Properties, Electrochemical Impedance Spectroscopy, Manufacturing Process, Surface Modification Materials Science, Mechanical Engineering, Manufacturing.
Keywords: Corrosion and anti-corrosives.; Building materials -- Corrosion.; elektronické knihy; electronic books